ANALISIS PENGENDALIAN KUALITAS UNTUK MEMINIMALISIR JUMLAH DEFECT PRODUK X PADA PT XYZ DENGAN PENDEKATAN QUALITY CONTROL CIRCLE - Ericho Verdy Ananda (2023)
This study aims to identify defective product quality problems and provide suggestions for improvement. Starts with the identification of the dominant and non-dominant causes of defects at PT XYZ is carried out using the Quality Control Cirlce method with the PDCA approach and in the improvement process using the help of seven tools or seven tools. The method of identifying the causes of dominant and non-dominant defects based on the pareto diagram, it can be seen that the most dominant defect is the stuck material with a percentage of 37.8%, Not Good Rope 28.2%, and broken rubber 23.6%. From the results of planning with seven tools, the next step is to look for factors that cause the appearance of defective products. In the improvement stage, it can be found that the factors that cause defects are the Machine, Human, Material, Method, and Environment factors based on the fishbone diagram. from these factors, improvements are made in the form of preparing machine maintenance schedules, preparing the latest fixed procedures or SOPs, and compiling machine maintenance work instructions.